The Role Of Interest And Talent Guidance For Pkh Kpm Children In Increasing Motivation To Continue To Higher Education - Salwa Khoerunnisa; Yandi Cahya Yundani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study aims to determine the role of interest and talent guidance in helping to increase the motivation of children of Beneficiary Families (KPM) of the Family Hope Program (PKH) to continue their education to university. This study used a qualitative, descriptive approach. The subjects were PKH beneficiary families (KPM PKH). Data collection techniques were observation, interviews, and documentation. Data analysis used the stages of data reduction, data presentation, and conclusion drawing. The results showed that before being provided with guidance, some PKH beneficiary children did not have a strong interest in continuing their education to university. This was indicated by some children preferring to work directly and experiencing confusion in determining further education options. This condition was influenced by a lack of information about universities, low motivation to continue their education, and economic factors. After the provision of interest and talent guidance, children began to show an increased understanding of their potential and an emerging interest in planning for higher education. Thus, interest and talent guidance plays a crucial role in helping PKH beneficiary children recognize their potential and increase their motivation to continue their education to university.